A Typological Analysis of Dairy Farms Based on Bulk Milk Price - V. D. V. Costa; R. R. Martinelli; F. I. Bánkuti (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study sought to examine the relationship between typological characteristics of dairy farms and the price received per liter of bulk milk in transactions with processing companies. During a period from January to March 2018, a total of 143 dairy farmers in western São Paulo State were interviewed on-site using a semi-structured questionnaire containing questions regarding structural, productive, and socioeconomic characteristics of farms and farm operators. Dairy farms were classified into two groups: G1 (n= 129), farms paid below the regional average price per liter of milk; and G2 (n= 14), farms paid above the regional average price per liter of milk. Then, factor analysis was used to extract factors associated with each dairy farm group. Three factors were identified: F1, Milk volume and quality; F2, Road conditions; and F3, Production area. Mean factor scores were compared by the Mann–Whitney U-test (p<0.05). G1 and G2 dairy farms differed significantly in Milk volume and quality (F1). There were no significant differences between G1 and G2 for the other factors. Dairy farms that produced a greater volume of milk and invested more in milk quality secured better prices in transactions with the industry. Based on these findings, it is concluded that actions to increase the scale of production and improve milk quality should be regarded as a priority, thereby increasing the likelihood that dairy farms will remain in business in the long term.